Os contos de fadas como mediadores na construção da moralidade em crianças da educação infantil - Souza, Juliana Damasceno e [UNESP] (2018)
At the moment a person chooses to read to a child, it must be borne in mind that it is not enough to oralize written history without first having a moment of reflection and personal study about which goals we want to achieve in relation to the reading. This research aims to provide the professional and non-educational reader with an awareness, enabling them to discover a pedagogical function aimed at the development of children's morality, through the answer of the problem question of the present work: Fairy Tales can be characterized as mediators in the construction of morality in children's Early Childhood Education? To this end, how should they be used by teachers? The referred research is a qualitative case study, being appropriate when the researcher has low control of the situation, that is inserted in a social context and is concerned with the understanding of a phenomenon, in this way, the objectives surround between verifying the possible use of Fairy Tales as mediators in the construction of moral autonomy in children's Early Childhood Education and to know and analyze the conception of a teacher about fairy tales as possible mediators in the moral development of the students. When you keep in mind Fairy Tales as instruments and all the achievements it could conquer, you must use them at appropriate times, such as before, during, or after the reading.. The present paper shows it can be used as mediators in the moral development of children, realizing, when carried out with specific goals and proper planning, can assist in the development of interpretation and in the critical capacity of children, in addition to contribute to social and moral constructions.